Modeling of carbon monoxide oxidation process on the two-dimensional catalyst surface - Kostrobij, P.; Ryzha, I. (Publishing House of Lviv Polytechnic National University, 2016)
In this paper the two-dimensional mathematical model for carbon monoxide (CO) oxidation on the surface of Platinum (Pt) catalyst is investigated accounting for the processes of the catalyst surface reconstruction and the effect of the substrate temperature. It is shown that the stability region for reaction of CO oxidation changes in two-dimensional case. Дослiджено двовимiрну математичну модель оксидацiї чадного газу (СО) на поверхнi платинового каталiзатора з урахуванням процесiв перебудови поверхнi каталiзатора та впливу температури пiдложки. Показано, що в двовимiрному випадку область стiйкостi реакцiї окислення СО змiнюється.
Моделювання процесу оксидацiї чадного газу на двовимiрнiй поверхнi каталiзатора
Keywords: reaction of catalytic oxidation; reaction-diffusion model; mathematical modelling of reaction-diffusion processes; каталiтична реакцiя окислення; реакцiйно-дифузiйна модель; математичне моделювання реакцiйно-дифузiйних процесiв; 538.9